Strong m-Convexity of Set-Valued Functions - Lara Teodoro; Merentes Nelson; Quintero Roy; Rosales Edgar (Annales Mathematicae Silesianae, 2023)
In this research we introduce the concept of strong m-convexity for set-valued functions defined on m-convex subsets of real linear normed spaces, a variety of properties and examples of these functions are shown, an inclusion of Jensen type is also exhibited.